Pengaruh Parameter Proses Terhadap Kekasaran Permukaan Menggunakan Filamen PETG (Polyethylene Terephthalate Glycol) - Aji, Bayu; Pristiansyah, Pristiansyah; Ariyani, Yang Fitri (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
3D printing is a manufacturing process technology that has been developed to create a fast prototype according to the desired design, one of which is FDM (Fused Deposition Modeling) technology. Fused Deposition Modeling (FDM) technology is a printing technique used to print products using fibrous materials, the printed products have ideal geometric characteristics. The working principle of FDM is by extruding thermoplastic through a nozzle at a melting temperature, then the product is printed layer by layer. In this study the filament used is PETG (Polyethylene Terephthalate Glycol) filament. In this study using the Taghuci L9(4^3) OA method. This study aims to determine the most optimal process parameters with the parameters used in surface roughness testing according to the process parameters used, namely Nozzle Temperature, Flowrate, Printing Speed, Layer Thickness. the results of the research that has been carried out show the optimum parameter values for surface roughness, namely Nozzle Temperature (230℃), Flowrate (110%), Printing Speed (40mm/s), Layer Thickness (0.15mm).